2004
DOI: 10.1021/jm049717d
|View full text |Cite
|
Sign up to set email alerts
|

Time-Related Differences in the Physical Property Profiles of Oral Drugs

Abstract: Comparisons of the calculated physicochemical properties of oral drugs launched prior to 1983 (864 drugs) and between 1983 and 2002 (329 drugs) show that mean values of lipophilicity, percent polar surface area and H-bond donor count are the same, suggesting that these are the most important oral druglike physical properties. In contrast, mean values of molecular weight and the numbers of O + N atoms, H-bond acceptors, and rotatable bonds and rings have increased in 1983-2002 drugs (by 13-29%). Analysis of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
245
0
4

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 292 publications
(268 citation statements)
references
References 43 publications
15
245
0
4
Order By: Relevance
“…A wealth of scholarship exists about the differences in the physical chemical properties of CNS versus nonCNS drugs (21)(22)(23) and in fact, a number of computed properties vary signifi cantly between the two groups. Compounds possessing molecular parameters outside of the "ideal" ranges for CNS drugs tend to either have poor passive diffusion through cell membranes or to be substrates for MDR1 mediated effl ux.…”
Section: Discussionmentioning
confidence: 99%
“…A wealth of scholarship exists about the differences in the physical chemical properties of CNS versus nonCNS drugs (21)(22)(23) and in fact, a number of computed properties vary signifi cantly between the two groups. Compounds possessing molecular parameters outside of the "ideal" ranges for CNS drugs tend to either have poor passive diffusion through cell membranes or to be substrates for MDR1 mediated effl ux.…”
Section: Discussionmentioning
confidence: 99%
“…7,12,13,14,15 This important observation implies that lipophilicity is a fundamental property impacting the progress of drug discovery programs and the developability of identified candidates. In contrast, it has been observed that the physicochemical properties of analogues in a chemical series, including molecular weight and lipophilicity, often increase during optimisation from hit to lead 23 and lead to candidate.…”
Section: Lipophilic Ligand Efficiencymentioning
confidence: 99%
“…7,12,13,14,15 The median and mean molecular weight of approved drugs has risen by only around 50Da (15%) over the past 3 decades, whilst the median and mean molecular weight of synthesized experimental compounds has risen by over 100Da (30%). 16 In contrast, the molecules being published in the literature, 15 and patented by the pharmaceutical industry, 17 as well as those entering clinical development pipelines, 10 are more lipophilic, larger, and less three-dimensional 14,18 than approved oral drugs.…”
Section: Introductionmentioning
confidence: 99%
“…We will continue this work in the future by a quantitative calculation. [60] A quantitative characterization based on computed physicochemical property profiles such as Polarizability [29], Partition Coefficient (log P) [30][31][32][33], Hydration Energy [34][35][36], Molecular Volume [37], Molecular Surface and Molecular Mass [38] has been conducted. The physicochemical parameters used in the study are described below.…”
Section: Study Of Structure -Activity Relationships For 16-memberementioning
confidence: 99%